2012
DOI: 10.1177/1077801212437016
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Perceptions of Safety and Risk Following Police Intervention for Intimate Partner Violence

Abstract: Police intervention is a primary response to intimate partner violence (IPV) but does not guarantee a victim's future safety. This study sought to identify factors associated with IPV survivors' perceptions of safety and risk of revictimization following police intervention. One hundred sixty-four women completed a questionnaire, and 11 of those women also took part in qualitative interviews. The findings revealed that feeling unsafe and perceiving oneself to be at risk of future violence is associated with ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 43 publications
6
41
0
2
Order By: Relevance
“…Coker and colleagues (2000) suggested that sexual violence may be associated with escalation of physical violence. Dichter and Gelles (2012) and Harding and Helweg-Larsen (2008) both found sexual violence from an intimate partner, but not physical or psychological IPV, to be associated with women perceiving themselves to be at risk of future IPV.…”
Section: Ipv Victimization and Health Outcomesmentioning
confidence: 89%
“…Coker and colleagues (2000) suggested that sexual violence may be associated with escalation of physical violence. Dichter and Gelles (2012) and Harding and Helweg-Larsen (2008) both found sexual violence from an intimate partner, but not physical or psychological IPV, to be associated with women perceiving themselves to be at risk of future IPV.…”
Section: Ipv Victimization and Health Outcomesmentioning
confidence: 89%
“…In the study by Mertin and Mohr (2001) with 100 abused women who sought help at a shelter in Australia, 59 % stated they believed they might be murdered by their partners. Feeling unsafe and perceiving oneself to be at risk of future violence has been associated with experiencing particular forms of IPV including battering, lethality threats and sexual violence (Dichter 2010;Dichter and Gelles 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is known female victims of IPV do not always assess, in a realistic way, the severity of the situation they are experiencing (e. g., Campbell 2004). It has also been demonstrated that the belief of being in a situation of danger is associated with particular types of IPV (Dichter 2010;Dichter and Gelles 2012). However, few empirical studies have taken into consideration whether or not the woman has felt a threat to her life in the intimate relationship.…”
mentioning
confidence: 96%
“…Providing safety for themselves and their children is a constant source of stress for women in abusive relationships (Cronholm & Bowman, 2009;Ramaswamy, Kelly, Koblitz, Kimminau, & Engelman, 2011). Police intervention often is requested but does not necessarily solve the long-term problem because abused women may continue to live in fear of retaliation and revictimization (Dichter & Gelles, 2012). Prolonged stress, fear, and depression experienced by abused women can trigger complex neuroendocrine and immune system responses that decrease cytotoxic T-cell and natural killer-cell activities, making those women more susceptible to cancer and other health concerns (Reiche, Nunes, & Morimoto, 2004;Woods, 2005).…”
Section: Psychological and Emotional Factorsmentioning
confidence: 99%
“…Prolonged stress, fear, and depression experienced by abused women can trigger complex neuroendocrine and immune system responses that decrease cytotoxic T-cell and natural killer-cell activities, making those women more susceptible to cancer and other health concerns (Reiche, Nunes, & Morimoto, 2004;Woods, 2005). Social support has been found to decrease depression and improve quality of life for abused women (Beeble, Bybee, Sullivan, & Adams, 2009;Dichter & Gelles, 2012). Social support has been found to decrease depression and improve quality of life for abused women (Beeble, Bybee, Sullivan, & Adams, 2009;Dichter & Gelles, 2012).…”
Section: Psychological and Emotional Factorsmentioning
confidence: 99%